Cost‐effectiveness of mifepristone and misoprostol versus misoprostol alone for the management of missed miscarriage: an economic evaluation based on the MifeMiso trial. (7th June 2021) - Okeke Ogwulu, CB; Williams, EV; Chu, JJ; Devall, AJ; Beeson, LE; Hardy, P; Cheed, V; Yongzhong, S; Jones, LL; La Fontaine Papadopoulos, JH; Bender‐Atik, R; Brewin, J; et al.
Abstract : Objective: To assess the cost‐effectiveness of mifepristone and misoprostol (MifeMiso) compared with misoprostol only for the medical management of a missed miscarriage. Design: Within‐trial economic evaluation and model‐based analysis to set the findings in the context of the wider economic evidence for a range of comparators. Incremental costs and outcomes were calculated using nonparametric bootstrapping and reported using cost‐effectiveness acceptability curves. Analyses were performed from the perspective of the UK's National Health Service (NHS). Setting: Twenty‐eight UK NHS early pregnancy units. Sample: A cohort of 711 women aged 16–39 years with ultrasound evidence of a missed miscarriage. Methods: Treatment with mifepristone and misoprostol or with matched placebo and misoprostol tablets. Main outcome measures: Cost per additional successfully managed miscarriage and quality‐adjusted life years (QALYs). Results: For the within‐trial analysis, MifeMiso intervention resulted in an absolute effect difference of 6.6% (95% CI 0.7–12.5%) per successfully managed miscarriage and a QALYs difference of 0.04% (95% CI −0.01 to 0.1%). The average cost per successfully managed miscarriage was lower in the MifeMiso arm than in the placebo and misoprostol arm, with a cost saving of £182 (95% CI £26–£338). Hence, the MifeMiso intervention dominated the use of misoprostol alone. The model‐based analysis showed that the MifeMiso intervention is preferable, compared with expectant management, and this is the current medical management strategy. However, the model‐based evidence suggests that the intervention is a less effective but less costly strategy than surgical management. Conclusions: The within‐trial analysis found that based on cost‐effectiveness grounds, the MifeMiso intervention is likely to be recommended by decision makers for the medical management of women presenting with a missed miscarriage. Tweetable abstract: The combination of mifepristone and misoprostol is more effective and less costly than misoprostol alone for the management of missed miscarriages. Tweetable abstract: The combination of mifepristone and misoprostol is more effective and less costly than misoprostol alone for the management of missed miscarriages.